2015
DOI: 10.1016/j.mbs.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance as collateral damage: The tragedy of the commons in a two-disease setting

Abstract: We propose a simple two-disease epidemic model where one disease exhibits only a drug-sensitive strain, while the other exhibits both drug-sensitive and drug-resistant strains. Treatment for the first disease may select for resistance in the other. We model antibiotic use as a mathematical game through the study of individual incentives and community welfare. The basic reproduction number is derived and the existence and local stability of the model equilibria are analyzed. When the force of infection of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Under both treatment strategies, it is shown that for model (2.1) with the restriction (H) the uninfected population is always increased by choosing a higher treatment rate; this differs from the two-disease model we studied in [17]. …”
Section: Noninteracting Transmissionmentioning
confidence: 81%
See 1 more Smart Citation
“…Under both treatment strategies, it is shown that for model (2.1) with the restriction (H) the uninfected population is always increased by choosing a higher treatment rate; this differs from the two-disease model we studied in [17]. …”
Section: Noninteracting Transmissionmentioning
confidence: 81%
“…In our model, there are four epidemiological classes: susceptible to both diseases, susceptible to disease 2 but infectious for disease 1, susceptible to disease 1 but infectious for disease 2, and infectious for both diseases. It is a simplified version of the two-disease three-strain model in Gao et al [17] in which the first disease exhibits both drug sensitive and resistant strains. The cotransmission dynamics of two diseases modeled as a SIS process is of interest as a simplified model of, for instance, ocular chlamydia [33, 32, 34] and respiratory pneumococcal colonization [36].…”
Section: Discussionmentioning
confidence: 99%
“…uk/downloads/CS47131-NHSNHCCG-Antibiotic-Guidelines-2018-WHOLE-PRF5.pdf?fbclid¼IwAR2M_ACCx2G17VvvYwwZkJiss6KhOjDLt4w0wTFIBWFRxOkg71OvK6rZw3M. 7 Public Health England. Start Smart Then Focus Appendix 1.…”
Section: Use Social and Reputationalmentioning
confidence: 99%
“…Variations of the term proportion in this subset include 'fraction', 'frequency', or 'prevalence' of resistance; likewise, variants of the term resistant patients including 'colonisation with resistant bacteria', 'resistant infections' or 'resistant strains' were assigned to this outcome category. Additional outcomes of interest include the likelihood of and/or time to resistance emergence or extinction [ Macrolides - [82,84,93] Erythromycin [90,103] Mixed infections Carbapenems Ertapenem [35,88] Penicillins Piperacillin [35,88] (Continued ) 2020 D. E. Ramsay et al…”
Section: Model Output and Validationmentioning
confidence: 99%